2020
DOI: 10.1002/jsid.958
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic study of patterns based on event‐related potential and eye‐tracking: Taking the decorative patterns of the Tang dynasty as an example

Abstract: The decorative patterns of Tang dynasty (DPTD) combine Chinese and western styles, providing inspirations to designers. The main purpose of the study is to summarize aesthetic cognition for DPTD and improve modern Tang style products design, thus introducing new materials and ideas to modern products design. The event‐related potential (ERP) and eye‐tracking were mainly used to study DPTD, exploring early reactions of brain nerves in the process of aesthetic cognition of DPTD, and analyze people's aesthetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In EEG-ET combined experimental studies, it is necessary to connect the collection equipment, stimulus presentation equipment, behavior-recording equipment, and other hardware devices to ensure the stability and accuracy of the data. Before the experiment starts, the layout of the EEG electrodes and the position of the stimulus presentation device need to be designed to minimize signal transmission and interference between different hardware devices [46]. The electrode cap is worn on the subject's head, and there are two types of eye-tracking instruments, mobile and fixed, which are respectively worn on the eyes and fixed above the computer monitor used for target experiments.…”
Section: Preprocessing Methods and Device Connectionsmentioning
confidence: 99%
“…In EEG-ET combined experimental studies, it is necessary to connect the collection equipment, stimulus presentation equipment, behavior-recording equipment, and other hardware devices to ensure the stability and accuracy of the data. Before the experiment starts, the layout of the EEG electrodes and the position of the stimulus presentation device need to be designed to minimize signal transmission and interference between different hardware devices [46]. The electrode cap is worn on the subject's head, and there are two types of eye-tracking instruments, mobile and fixed, which are respectively worn on the eyes and fixed above the computer monitor used for target experiments.…”
Section: Preprocessing Methods and Device Connectionsmentioning
confidence: 99%
“…Eye-tracking can capture objective and real-time data of visual attention, and it is also an indicator of good behavior in information acquisition, which is considered to be closely related to higher-order cognitive processes ( Baek and Ok, 2017 ). Commonly used eye-tracking measurement indicators are fixation duration, fixation count, pupil size, etc., which reveal different aspects of visual esthetic and esthetic emotion ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Eye-tracking is an eye sensor technology in which attention or other mental states are inferred from eye position data, offering insight into individual aesthetic activities. Studies have found that pupil size, as one variable measured using eye tracking, is related to aesthetic preferences regarding artworks [37,38] . For instance, Ho and Lu [39] found that the index of pupil size could be used to distinguish different degrees of aesthetic stimulation, indicating that pupil size was related to aesthetic activities.…”
Section: Research Using Multi-mode Hybrid Technologymentioning
confidence: 99%
“…Studies have found that pupil size, as one variable measured using eye tracking, is related to aesthetic preferences regarding artworks. [37,38] For instance, Ho and Lu [39] found that the index of pupil size could be used to distinguish different degrees of aesthetic stimulation, indicating that pupil size was related to aesthetic activities. Specifically, when the degree of arousal was high, the participants attended to an image of an unpleasant scene for longer than an image of a pleasant scene, while the opposite was observed when the degree of arousal was low.…”
Section: Research Using Multi-mode Hybrid Technologymentioning
confidence: 99%